THE ROLE OF THE CONCEPT OF COLLECTIVE SECURITY IN INTERNATIONAL LAW AND LEGAL ISSUES OF ITS IMPLEMETTAION - Zakaryan, Armen (State and Law, 2020)
The concept of collective security represents international arrangments defininginternational peace and security threats and the collective means of struggle againstthese threats. The key issues hindering implementation of collective security andeffective functioning of the United Nations and the Security Council - its key bodyresponsible for international peace and security are considerably high. If we group theinternational legal issues that hinder the implementation of the collective securityconcept, they may be divided into the following main groups: the UN SecurityCouncil's decision-making procedures, in particular, the abuse of the veto right by theUN Security Council permanent members, attempts to create new grounds for the useof force and misuse of individual/collective self-defense.
Keywords: collective security concept, UN Security Council, abuse of vetto right, humanitarian intervention, duty to protect, misuse of self-defense